A case report on Fibular Aplasia, Tibial Campomelia, Oligosyndactyly Syndrome variant in a Male Infant - Mumtaz Hashmi, Hina; Shamim, Nazia; Kumar, Vinod; Mirza, Adnan; Kirmani, Salman; Irfan, Babar; Hasan, Hania (Journal of the Pakistan Medical Association, 2022)
Fibular aplasia, tibial campomelia, and oligosyndactyly (FATCO syndrome) is a rare, genetic, congenital limb malformation characterized by unilateral or bilateral fibular aplasia, tibial campomelia, and lower limb oligosyndactyly involving the lateral rays. A newborn male born at term via a Caesarean Section presented with malformations consisting of tibial campomelia, unilateral fibular hypoplasia, and oligosyndactyly, a “FATCO variant” case. On radiographic examination, an anterolateral shortened and bowed right lower limb at the distal third of the tibia, a rudimentary right fibula and absence of three rays on right foot were revealed. “FATCO syndrome” although rare may be linked to involvement of different body systems with morbidity and mortality. Proper parent counseling is a key aspect of this syndrome. Timely diagnosis and management with a multidisciplinary approach is essential to avoid lifelong disability, which can be a hurdle in a developing country.